Differentials and trends in emergency department visits due to alcohol intoxication and co-occurring conditions among students in a U.S. public university. (1st February 2018) - Ngo, Duc Anh; Ait-Daoud, Nassima; Rege, Saumitra V.; Ding, Christopher; Gallion, Lauren; Davis, Susan; Holstege, Christopher P.
Highlights: First study to link student emergency department (ED) medical records with the admission dataset. There was a rising trend in student ED visits involving alcohol intoxication. Variations observed in the rate of intoxication by campus-related factors. Nearly one fourth of student ED visits with alcohol intoxication involving injuries. Abstract: Background: Few studies have explored the epidemiology of students presenting to the emergency department (ED) as a consequence of hazardous drinking. This study examined differentials and trends in ED visits following alcohol intoxication and co-occurring conditions among students presenting to a major U.S. university health system. Methods: The ED electronic medical records from academic years 2010–2015 were queried for student visits and their records were linked to the university's student admission datasets. Student alcohol-related visits were identified based on ICD-9 codes. Student characteristics and trends in the rate of alcohol intoxication per 100 ED student visits were analyzed. A random sample of 600 student clinical records were reviewed to validate diagnostic codes. Results: There were 9616 student ED visits (48% males) to the ED of which 1001 (10.4%) visits involved alcohol intoxication. Two thirds of ED visits with alcohol intoxication had a co-occurring diagnosis, with injuries (24%) being the most common condition. The rate of alcohol intoxication varied greatly by student demographics and campus-related factors. There was a linear increase in the rate of alcohol intoxication from 7.9% in 2009–10 to 12.3% in 2014–15 (p < 0.01). The increase was greater among female students, students below 20 years of age, Asian students, and student athletes. In the sample reviewed, only two thirds of ED visits with alcohol intoxication were recorded by diagnostic codes. Conclusion: The rate of ED visits following alcohol intoxication varied by student demographic characteristics and campus-related factors with a rising trend over the study period.